2021
DOI: 10.18805/lr-4464
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Incidence of Pulse Aphid (Aphis craccivora Koch.) and its Natural Enemies on Field Pea (Pisum sativum L.) in Relation to Some Abiotic Factors in Alluvial Zone of West Bengal

Abstract: Background: Field pea, Pisum sativum L. is an important winter-season pulse crop. It is subjected to damage by both field and storage insect pests and approximately 10-15 per cent reduction in yield was reported due to the infestation of different insect pests. Among these, pulse aphid (Aphis craccivora Koch.) affects plant physiology directly by removal of nutrients or indirectly by dispersal of various viral diseases. The present investigation has been aimed to study the seasonal fluctuations of aphids and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They also reported a positive correlation between larval population and a negative correlation with relative humidity. Pal et al (2021) also reported the similar conclusion that abiotic factors are the main determining factors of the incidence of pest population. Similarly, Umbarkar et al (2010) investigated the seasonal incidence of H. armigera in kharif-2018 and found out the highest incidence was observed at 31 st standard week which exhibit highly significant negative correlation with minimum temperature and evening relative humidity.…”
Section: Seasonal Incidence Of S Litura In Field Correlated With Weat...mentioning
confidence: 60%
“…They also reported a positive correlation between larval population and a negative correlation with relative humidity. Pal et al (2021) also reported the similar conclusion that abiotic factors are the main determining factors of the incidence of pest population. Similarly, Umbarkar et al (2010) investigated the seasonal incidence of H. armigera in kharif-2018 and found out the highest incidence was observed at 31 st standard week which exhibit highly significant negative correlation with minimum temperature and evening relative humidity.…”
Section: Seasonal Incidence Of S Litura In Field Correlated With Weat...mentioning
confidence: 60%